2009
DOI: 10.1016/j.rmed.2008.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Drop-out and attendance in pulmonary rehabilitation: The role of clinical and psychosocial variables

Abstract: In general, adherence in rehabilitation is high. However, paying attention to patients' nutritional status and creating a positive expectation of treatment during referral and intake appear to be important if one aims to optimise patients' attendance during rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
138
5
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(163 citation statements)
references
References 41 publications
12
138
5
1
Order By: Relevance
“…Twentythree (37%) of our initial 63 patients dropped out. That drop-out ratio is somewhat higher than that observed by Fischer et al 34 and Pitta et al, 3 but much lower than that observed by Bourbeau et al 35 and Cote and Celli, 36 who had drop-out rates of up to 60%. The drop-out rates did not differ between the 2 groups (35% in the calisthenics-andbreathing group, 38% in the endurance-and-strength group), which conflicts with the expectation that a lower-intensity training program should have a lower drop-out rate and higher adherence than a higher-intensity program.…”
Section: Discussioncontrasting
confidence: 51%
“…Twentythree (37%) of our initial 63 patients dropped out. That drop-out ratio is somewhat higher than that observed by Fischer et al 34 and Pitta et al, 3 but much lower than that observed by Bourbeau et al 35 and Cote and Celli, 36 who had drop-out rates of up to 60%. The drop-out rates did not differ between the 2 groups (35% in the calisthenics-andbreathing group, 38% in the endurance-and-strength group), which conflicts with the expectation that a lower-intensity training program should have a lower drop-out rate and higher adherence than a higher-intensity program.…”
Section: Discussioncontrasting
confidence: 51%
“…The attainment of individual independence, social participation, and skills at the highest level and their continuation are the targets of PR programs (7). Despite its many proven effects, it was reported in the literature that the rate of participation in PR fell to 50% and the discontinuation rate was 23-31% (8)(9)(10). In the studies conducted, transportation, work conditions, a level of increased shortness of breath, and low social support were observed to be among the reasons for noncompliance and nonattendance in PR programs (8,9,(11)(12)(13).…”
Section: Discussionmentioning
confidence: 96%
“…Despite its many proven effects, it was reported in the literature that the rate of participation in PR fell to 50% and the discontinuation rate was 23-31% (8)(9)(10). In the studies conducted, transportation, work conditions, a level of increased shortness of breath, and low social support were observed to be among the reasons for noncompliance and nonattendance in PR programs (8,9,(11)(12)(13). Those who have transportation and work problems or a high level of perception of shortness of breath as well as advanced-stage and bedbound cases also benefit from PR by means of supervised home-based, remotely supervised, and unsupervised programs.…”
Section: Discussionmentioning
confidence: 99%
“…The PEP program is currently in 262 PR centers (232 active) in 44 states with more than 5000 individuals enrolled in the program in 2015. Pulmonary rehabilitation is built around a relationship of education, exercise, coping skills, and social bonding. A patient will typically have [12][13][14][15][16][17][18][19][20][21] sessions. After graduation, they receive a graduation kit and continue to receive long term benefits.…”
Section: Lessons Learned From Pulmonary Education Program and On Tracmentioning
confidence: 99%
“…15 A total of 30% of patients declined to attend even the first visit. Half of the patients reported not receiving PR information at the time of referral.…”
mentioning
confidence: 99%